Potensi Konversi Limbah Organik dengan Metode Pirolisis Menjadi Biochar, Syngas dan Bio-Oil: Tinjauan Literatur Sistematis - Masrida, Reni; Kartika, Wahyu (LPPMP Universitas Bhayangkara Jakarta Raya, 2025)
Indonesia has a major challenge in organic waste management, with household waste being the main component. Pyrolysis methods offer a promising solution to address this problem by converting organic waste into valuable products such as biochar, syngas, and bio-oil. This article analyzes the potential of pyrolysis methods in managing organic waste in Indonesia, including the physicochemical characteristics and applications of pyrolysis products. A systematic literature study was used to review various sources related to organic waste treatment. Pyrolysis is the thermal decomposition of organic materials under oxygen-poor conditions at high temperatures (300-700°C), producing biochar, bio-oil, and syngas. This method provides a more environmentally friendly alternative to incineration and landfilling, with a wide range of potential applications for the resulting products.